IMPLEMENTATION OF SELF-MANAGEMENT PRACTICES TO IMPROVE CORPORATE CULTURE - BILYK, Victoriia; SHPILEVA, Vira; ANHELSKA, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the course of writing the scientific article, the main stages of implementing self-management practices to improve corporate culture were determined. It was found that the effectiveness of such practices largely depends on the level of organizational support and adaptation to specific conditions. Key aspects affecting the success of self-management implementation, including personnel motivation, adaptation to military challenges, and changes in the corporate structure, are analyzed. The study showed that the implementation of self-management strategies makes it possible to increase the adaptability of organizations to the rapidly changing conditions of war, contributing to the preservation and improvement of corporate culture even in difficult and unstable conditions. The key aspects of the implementation of such practices are summarized, which is an important factor for maintaining the stability and efficiency of organizations in the conditions of a long war. The impact of self-management on various aspects of corporate culture in the context of war is systematized, in particular, on the interaction between employees, management processes and the general atmosphere in the organization. The results of the study indicate the need for full or partial integration of various self-management practices into the general management strategies of Ukrainian organizations, which allows them to effectively cope with challenges arising in crisis situations caused by war.
Keywords: self-management; corporate culture; adaptability; crisis phenomena; management processes; sustainability; competitiveness